The Role of NcRNAs to Regulate Immune Checkpoints in Cancer - Jiang, Yicun; Zhao, Leilei; Wu, Yiwen; Deng, Sijun; Cao, Pu; Lei, Xiaoyong; Yang, Xiaoyan (Frontiers in Immunology, 2022)
At present, the incidence of cancer is becoming more and more common, but its treatment has always been a problem. Although a small number of cancers can be treated, the recurrence rates are generally high and cannot be completely cured. At present, conventional cancer therapies mainly include chemotherapy and radiotherapy, which are the first-line therapies for most cancer patients, but there are palliatives. Approaches to cancer treatment are not as fast as cancer development. The current cancer treatments have not been effective in stopping the development of cancer, and cancer treatment needs to be imported into new strategies. Non-coding RNAs (ncRNAs) is a hot research topic at present. NcRNAs, which include microRNAs (miRNAs), circular RNAs (circRNAs), and long non-coding RNAs (lncRNAs), participate in all aspects of cancer biology. They are involved in the progression of tumors into a new form, including B-cell lymphoma, glioma, or the parenchymal tumors such as gastric cancer and colon cancer, among others. NcRNAs target various immune checkpoints to affect tumor proliferation, differentiation, and development. This might represent a new strategy for cancer treatment.